Utilizing Macrophages Missile for Sulfate-Based Nanomedicine Delivery in Lung Cancer Therapy - Liu, Chang; Chen, Yongyang; Xu, Xiaoyu; Yin, Miao; Zhang, Hongbo; Su, Wenmei (American Association for the Advancement of Science, 2025)
Nanomaterial-based drug delivery systems are susceptible to premature drug leakage and systemic toxicity due to lack of specific targeting, and live-cell drug delivery is also prone to be restricted by drug-carrier cell interactions. Here, a method is established to adsorb drug-loaded nanomaterials externally to the live cells, which reduces cytotoxicity caused by drug uptake and improves the bioactivity of the carrier cells and drug release at the lesion site. It was found that polyphenols act like “double-sided tape” to bridge metalorganic frameworks (MOFs) nanoparticles with live macrophages (Mφ), attaching MOFs to the Mφ surface and minimizing intracellular uptake, with no negative effect on cell proliferation. On this basis, a “macrophage missile” with peroxymonosulfate (PMS) loaded MOFs nanoparticles on the cell surface was constructed. As a “propellant”, the Mφ, in which bioactivity is preserved, can selectively identify and target tumor cells, precisely bringing nanomedicines to the lesion. MOFs nanoparticles are used to load and catalyze PMS which acts as an exogenous source of reactive oxygen species (ROS), showing higher efficacy and lower toxicity in an oxygen-independent manner. The primary study results demonstrate that this innovative combination of biology and nanomaterials significantly enhances tumor targeting and therapeutic efficacy while reducing systemic side effects. This approach is expected to provide a more effective and safer treatment for lung cancer and holds promise for broader applications in other cancer therapies.